Potensi Pengembangan Tanaman Obat-Obatan Di Pekarangan Sebagai Upaya Peningkatan Agroindustri Perkotaan - Ratna Mustika Wardhani (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2020)
Abstract— The optimal use of yard is the best solution in providing added value for agro-industry products. One of the raw materials for agro-industry is medicinal plants. This study aims to determine the potential of medicinal plants planted in the yard and analyze the added value of medicinal plants grown in the yard into agro-industrial products. The method used is descriptive method that is applied in several regions that empower fruit, vegetable and medicinal plants as providers of agro-industrial raw materials, while the data analysis method uses the Value-Add Analysis method using the Hayami method (1987). After the research can be concluded as follows: (1) Identification of 15 types of medicinal plants, of which all types of medicinal plants can be used as agroindustry raw materials, namely Ginger, Turmeric, Sere, Pandan, Lengkuas, Aloe Vera, Kencur , Betel, Mustache cat, Tread Doro, Temu lawak, Temu Ireng, Kunci, Keji beling, Sambiroto. (2) Each research area has superior priority for the types of plants used as different raw materials, from the 3 highest priority sequences, namely: Ngawi Regency (Jahe, Kunyit, Sere), Magetan Regency (Ginger, Turmeric, Pandan) , Kabupaten Madiun (Ginger, Galangal, Turmeric), Madiun City (Ginger, Pandanus, Sere). (3) Processed products based on medicinal plants, namely Ginger into ginger syrup, are added value of Rp. 20250 - / kg, Turmeric plants become Jamu Kunyit in the amount of Rp. 19500 / kg, Pandanus plants become processed products of Pandan Dye amounting to Rp.46800 / kg. Keywords—: Medicinal Plants; Yard; Agroindustry.